2020
DOI: 10.1097/iae.0000000000002566
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Study of Intravitreal Aflibercept in Humans With Neovascular Age-Related Macular Degeneration

Abstract: Purpose: To investigate the half-life of aflibercept in aqueous humor after a single intravitreal injection in patients with neovascular age-related macular degeneration. Methods: Prospective, noncomparative, interventional case series of five eyes with neovascular age-related macular degeneration naive to anti–vascular endothelial growth factor therapy were enrolled and treated with intravitreal aflibercept. At baseline, best-corrected visual acuity, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 12 publications
2
35
1
Order By: Relevance
“…Molecular weight and parameter values used as a basis for simulations are summarized from published literature (Table 1). [2][3][4][5]7,8,[12][13][14][15][16][17][18][19][20][21][22] Initial vitreous molar drug concentrations were based on a vitreous volume of 4 mL and clinical doses of 2 mg for IVT-AFL, 6 mg for IVT-BRO, and 0.5 mg for IVT-RAN. Flip-flop PK relationships for each agent were assumed, consistent with Hutton-Smith et al 23 and Caruso et al, 24 with aqueous ≈ vitreous half-life for IVT-AFL and IVT-RAN, and serum ≈ vitreous half-life for IVT-BRO.…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular weight and parameter values used as a basis for simulations are summarized from published literature (Table 1). [2][3][4][5]7,8,[12][13][14][15][16][17][18][19][20][21][22] Initial vitreous molar drug concentrations were based on a vitreous volume of 4 mL and clinical doses of 2 mg for IVT-AFL, 6 mg for IVT-BRO, and 0.5 mg for IVT-RAN. Flip-flop PK relationships for each agent were assumed, consistent with Hutton-Smith et al 23 and Caruso et al, 24 with aqueous ≈ vitreous half-life for IVT-AFL and IVT-RAN, and serum ≈ vitreous half-life for IVT-BRO.…”
Section: Model Developmentmentioning
confidence: 99%
“…Selected aflibercept half-life for model: 9.1 days Rationale for selection: Do et al 13 is the only publication that reports the aqueous half-life of aflibercept in nAMD patients. The mean was used (a conservative estimate, but consistent with using the mean for other anti-VEGF) and the median of 11 days was examined in sensitivity analyses.…”
Section: Single-dose Pk Simulations After Intravitreal Dosingmentioning
confidence: 99%
“…A study conducted in five patients with AMD found an aqueous half-life of approximately nine days based on aqueous samples. They also found very low plasma levels, suggesting a lack of substantial plasma exposure [59].…”
Section: Pharmacokinetics Of Anti-vefg Drugsmentioning
confidence: 99%
“…Until now, there are no available data on the half-life of aflibercept in the human eye. e most recent study of Do et al has shown that the half-life of aflibercept in the aqueous humor after a single intravitreal injection in five patients with neovascular AMD was 11 days [16].…”
Section: Discussionmentioning
confidence: 99%